Chapter Bullismo etnico pregiudiziale: il ruolo di fattori individuali e contestuali - Taiti, Maria Chiara (Studies on Adult Learning and Education, 2022)
Multi-ethnic societies have the potential to enrich societies culturally (Mok et al. 2007), but they can also foster intolerance and anti-immigrant movements, where minorities may be more likely to be discriminated (Baysu et al. 2014; Rutland and Killen 2015) and bullied if this behaviour is repeated over time. A socio-ecological perspective becomes fundamental because the context, together with specific individual characteristics, contributes to maintaining negative attitudes towards those who belong to a different ethnic group. In this regard, the general objective of this study is to further investigate the phenomenon of ethnic bullying in adolescence and to shed light on the role played by the context and specific individual factors that are associated with it.